O SOME na comunidade de tartarugueiro em Ponta de Pedras/PA: entre o legal e o real observado - SILVA, Enely Tavares da (Universidade Federal do Pará, 2017)
This dissertation analyzes current processes high school implementation in Tartarugueiro community, Ponta de Pedras district, Marajó region, state of Para, which is being implemented by the State Secretariat of Pará State Education (SEDUC) through the System Modular Teaching Organization (SOME). Methodologically, the text was based on qualitative field research and bibliographical and documentary survey. Open and semi-structured interviews were conducted and observations on location at own research object community. The general conclusion reached was that in spite of the difficulties and problems for the implementation of the enrollment, the SOME is a possibility of increased schooling with entry prospects in the labor market and access to higher education, mainly due to the Maroons quota subject to the Tartarugueiro community in Ponta de Pedras, Para.